Hydrothermal and Coprecipitation Synthesis Design of BiVO4 for Methylene Blue Degradation - Riapanitra, Anung; Setyaningtyas, Tien; Haryanto, Michael Julian; Haryadinaru, Ghinatanitha Haqqu (Jurnal Riset Kimia, 2025)
This study investigated the characteristics and photocatalytic activity of BiVO4 photocatalyst synthesized using hydrothermal and coprecipitation methods for methylene blue (MB) degradation under visible light. The variation of synthesis parameters, including pH, calcination temperature, and pH of MB solution, affects the crystal structure, morphology, and photocatalytic efficiency of the material. XRD characterization results show that the hydrothermal method produces BiVO4 with pure scheelite(m-s) monoclinic phase and high crystallinity, while the coprecipitation method produces a combination of scheelite(m-s) monoclinic and orthorhombic Bi4V2O11 phases, which contributes to enhanced photocatalytic activity through better charge separation. The average crystal size of the hydrothermal method is 17.85 nm, larger than that of coprecipitation (11.41-14.71 nm), which gives the coprecipitated material a surface area advantage. SEM analysis showed rod-like morphology in hydrothermal, while coprecipitation produced sphere-grape-like particles. UV-Vis DRS results show that hydrothermal synthesized BiVO4 has a band gap energy of 2.28 eV, smaller than BiV(4)(400) (2.46 eV) and higher than BiV(4)(550) (2.07 eV) synthesized using coprecipitation method. This smaller band gap energy indicates that the interaction of Bi³⁺ and VO₄³- ions in the hydrothermal material is better, thus favoring visible light absorption. The highest photocatalytic activity was obtained from the coprecipitated material with a degradation efficiency of 89.32% at pH 11 within 150 min, higher than the hydrothermal material which reached 76.06% under similar conditions. This photocatalytic activity was dominated by OH* and O2-* radicals, which play a role in MB degradation. This study shows that designing synthesis pH parameters (4-7), calcination temperature (400), and coprecipitation method produced a material with optimum photocatalytic performance, making BiVO4 a superior candidate for colored wastewater treatment applications.